Optical Properties of Silver Nanowires Conjugated with Protein - Nga, Do Thi; Huy, Vu Van; Ha, Chu Viet (Communications in Physics, 2021)
Optical properties of protein-conjugated metallic nanowires are theoretically investigated based on the Mie theory and the core-shell model. Our numerical calculations show that optical spectra of protein-conjugated nanowires can have more a maximum compared to these nanowires without biomolecules. This finding is in a good agreement with previous experiments. We provide better interpretation for the origin of optical peaks in absorption spectrum of nanowires. Our results can be used for designing biosensors and bio-detectors.